Optimasi Perencanaan Pembangkit Listrik Tenaga Surya Atap On-Grid Melalui Simulasi PVsyst - Slamet Nurhadi; Priya Surya Harijanto; Mochamad Ferdy Hamzah (Politeknik Negeri Malang, 2025)
This study addressed the critical issue of Indonesia's persistent dependence on fossil fuels and the urgent need to accelerate New and Renewable Energy (NRE) adoption. The purpose of the research was to develop a comprehensive technical plan for a 1.202 kWp grid-tied rooftop photovoltaic (PV) system at a manufacturing facility in Karawang. The methodology employed a systematic approach consisting of site surveys, electrical configuration design (stringing, cabling, and protection systems compliant with PUIL 2020), and verification through PVsyst simulation software. Important findings revealed that the designed system projected an annual energy yield of 1,624,801 kWh with a Performance Ratio (PR) of 76.1%. The implications of this research suggested that the proposed rooftop PV system is technically robust and provides significant economic and environmental benefits, including an estimated annual revenue of IDR 1.68 billion and a reduction of 1,348.58 tons of CO2 emissions. These results demonstrated that large-scale industrial rooftop PV systems are a viable solution for achieving national energy transition goals